A Sufficient Criterion to Choose Quadratic Lyapunov Functions for Nonlinear Systems - Longhi, L.G.S.; Secchi, A.R. (Trends in Computational and Applied Mathematics, 2003)
A sufficient criterion to determine sign definiteness regions for multivariable scalar functions is presented.